Lectotypification of names related to Teucrium montanum L. (Lamiaceae) reported for the Balkan peninsula - Zbiljić, Miloš; Lakušić, Dmitar; Stevanoski, Ivana; Kuzmanović, Nevena (Phytotaxa, 2022)
Teucrium montanum is a species widely distributed in Europe, occurring also in North Africa and Asia Minor. Because of its wide distribution and high morphological variability, many taxa related to T. montanum have been described. In this paper we discuss and lectotypify the following six names of taxa described or reported for the Balkan Peninsula: T. helianthemoides, T. montanum var. hirsutum, T. montanum var. modestum, T. montanum var. parnassicum, T. pannonicum, and T. skorpilii.